2012
DOI: 10.1021/mz300311p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macrocyclic Polymers Formed via Intramolecular Radical Trap-Assisted Atom Transfer Radical Coupling

Abstract: The synthesis of cyclic polystyrene (PSt) with an alkoxyamine functionality has been accomplished by intramolecular radical coupling in the presence of a nitroso radical trap. Linear α,ω-dibrominated polystyrene, produced by the atom transfer radical polymerization (ATRP) of styrene using a dibrominated initiator, was subjected to chain-end activation via the atom transfer radical coupling (ATRC) process under pseudodilute conditions in the presence of 2-methyl-2-nitrosopropane (MNP). This radical trap-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…These results indicate that even in a large excess, substantial dimerization competes with end‐capping when MNP is used as the radical trap. This is not unexpected, as high amounts cyclization of dibrominated PS was found even in a much larger excess of MNP as the radical trap …”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…These results indicate that even in a large excess, substantial dimerization competes with end‐capping when MNP is used as the radical trap. This is not unexpected, as high amounts cyclization of dibrominated PS was found even in a much larger excess of MNP as the radical trap …”
Section: Resultsmentioning
confidence: 66%
“…Two radical traps, MNP and nitrosobenzne (NBz) were added in varying equivalents to redox active solutions of PSBr. Previous research by our group has shown that both MNP and/or NBz act as radical traps in ATRC‐like reactions leads to high amounts of coupling for end‐halogenated polystyrene (PS), poly(methyl methacrylate), and poly(methyl acrylate), producing either coupled polymer dimers or cyclic polymers. This so‐called RTA‐ATRC is summarized in Scheme , along with the desired nitroxide‐capped intermediate (boxed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic polymers can be prepared directly from dibrominated precursors, prepared by ATRP, in both ATRC [15] or RTA-ATRC [16,17] reactions. We have shown, as well, that RTA-ATRC can be successful in instances where ATRC fails.…”
Section: Scheme 1 Mechanistic Comparison and Rate Comparison Of Atrcmentioning
confidence: 99%
“…As an example, the conversion of the terminal alkyl bromide into an azide group when an alkyne-containing ATRP initiator is used allows for ring closure by "click" chemistry [45e48]. By choosing a dibrominated initiator, ATRP can be used to produce telechelic polymers that can be directly employed in end-to-end coupling reactions either by ATRC [49] or RTA-ATRC [50] resulting in cyclic (Scheme 2), or even dicyclic, polymers [27,51]. Ring closing by traditional ATRC to produce macrocycles is problematic due to the following: i) chain end radicals must terminate by head-to-head coupling and ii) chain end radicals must be sufficiently present (large K ATRP value) that a bimolecular reaction is feasible in which each chain end radical has only one allowable partner.…”
Section: Introductionmentioning
confidence: 99%